2016
DOI: 10.1007/s12010-016-2114-8
|View full text |Cite
|
Sign up to set email alerts
|

The WRKY Transcription Factor Family in Citrus: Valuable and Useful Candidate Genes for Citrus Breeding

Abstract: WRKY transcription factors belong to a large family of plant transcriptional regulators whose members have been reported to be involved in a wide range of biological roles including plant development, adaptation to environmental constraints and response to several diseases. However, little or poor information is available about WRKY's in Citrus. The recent release of completely assembled genomes sequences of Citrus sinensis and Citrus clementina and the availability of ESTs sequences from other citrus species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 70 publications
3
25
0
Order By: Relevance
“…Regarding the members of the CiuWRKY family, we have updated our previous results obtained by Ayadi et al (2016), who identified 51, 48, and only one WRKY TF in Citrus sinensis, C. clementina, and Citrus unshiu, respectively. On the other hand, da Silva et al (2017) found 77 WRKY genes from the Citrus sinensis genome, most of them classified in group I (36 CitsWRKYs), group II (35 CitsWRKYs), and group III (6 CitsWRKYs).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Regarding the members of the CiuWRKY family, we have updated our previous results obtained by Ayadi et al (2016), who identified 51, 48, and only one WRKY TF in Citrus sinensis, C. clementina, and Citrus unshiu, respectively. On the other hand, da Silva et al (2017) found 77 WRKY genes from the Citrus sinensis genome, most of them classified in group I (36 CitsWRKYs), group II (35 CitsWRKYs), and group III (6 CitsWRKYs).…”
Section: Discussionmentioning
confidence: 61%
“…For example, AtWRKY50 and AtWRKY51 are associated with the mechanism of repression between SA and JA (Gao et al, 2011). Also, CsWRKY41 and CsWRKY31 were both expressed in fruits, flowers, and leaves (Ayadi et al, 2016). Interestingly, CiuWRKY1, CcWRKY62, and CsWRKY42 genes are highly similar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, 77 WRKY genes were identified in the C. sinensis genome, 26 genes more than Ayadi et al (2016) (51 genes WRKY). The number of WRKY genes identified in sweet orange was similar to that in A. thaliana (72), higher than that in V. vinifera (59), and lower than that in O. sativa (96), Zea mays (119) and Populus trichocarpa (104).…”
Section: Discussionmentioning
confidence: 97%